The price of everything - McGoran, Jon (Solaris, 2025)
Corporations fall, gangsters are killed, but no-one messes with the Couriers Guild. When Armand Pierce first became a courier ten years ago, he had an attaché case connected to a titanium cuff grafted into the bones of his wrist, and took an oath: the delivery is everything. He can run, fight-kill, if he needs to-but the package gets where it's going. It's the Guild's guarantee, and since the internet went down in the Cyber Wars, all business, legitimate or otherwise, depends on it. Otherwise, he dies. So Pierce knows he's in deep trouble when he arrives at his latest destination to find his payload missing, his case mysteriously empty. Something strange is going on: something that's already cost three couriers their lives, and threatens to upend the global order. And Pierce had better get to the bottom of it, before the Guild, catches up to him.